Anti-idiotype antibodies in cancer treatment: the pharmaceutical industry perspective - Gómez, Roberto E.; Ardigo, Maria Laura (Frontiers in Oncology, 2012)
Active immunotherapy is an interesting field from the industry’s perspective and in the last years, regulatory agencies and the medical community have showed renewed expectations and interest in cancer vaccines. The development of new immune therapies offers many challenges, and this is reflected in the small number of phase III trials showing clear benefits. Traditional concepts applied in clinical trials for the development of chemotherapeutic agents may be inadequate for immunotherapies and a new paradigm is emerging. It is possible that organized efforts and funding will accelerate the development of therapeutically effective cancer vaccines. This article reviews the attributes of cancer vaccines which make them attractive from the industry´s perspective, and focuses especially in the characteristics of Racotumomab, an anti-idiotype antibody vaccine.